Predictive Indicators of Customer Loyalty in the Nigerian GSM Market - Ayodele; Adetola, Adeola; Esiti; Governor, Blankson (British Journal of Marketing Studies, 2016)
This study focuses on the predictive indicators of customer loyalty among GSM users in the South-Eastern Nigeria. Most of the studies on customer loyalty in the Nigerian GSM market are alien to South-Eastern Nigeria. The main objective of this study is to empirically inquire the factors that influence customer loyalty in the Nigerian GSM market. The study adopted survey research design and the population of study is the mobile phone users in Anambra State. Quota sampling method was employed while the sample size was determined using survey systems formula. Questionnaire was employed as the research instrument and the reliability test was achieved using split-half method. Factor analysis was used for data reduction and multiple regressions were employed to test the hypotheses. The findings revealed that trust, customer satisfaction, corporate image, service quality, network coverage have significant effect on customer loyalty with customer satisfaction as the strongest predictor of customer loyalty in the Nigerian GSM market. In addition, prompt customer service was seen to have no significant effect on customer loyalty. It was recommended that GSM service providers should focus more on customer satisfaction, trust, corporate image, service quality, and network coverage in order to build sustainable relationship with their customers as to become very competitive. Also, attention should be paid on providing quality customer care service elements.